2023
DOI: 10.1007/s13659-023-00373-4
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity against Fusarium oxysporum of quinolizidines isolated from three controlled-growth Genisteae plants: structure–activity relationship implications

Abstract: The Genisteae tribe belongs to the Fabaceae family. The wide occurrence of secondary metabolites, explicitly highlighting the quinolizidine alkaloids (QAs), characterizes this tribe. In the present study, twenty QAs (1–20), including lupanine (1–7), sparteine (8–10), lupanine (11), cytisine and tetrahydrocytisine (12–17), and matrine (18–20)-type QAs were extracted and isolated from leaves of three species (i.e., Lupinus polyphyllus ('rusell' hybrid), Lupinus mutabilis, and Genista monspessulana) belonging to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Alkaloid 2 significantly inhibited migration and invasion of human gastric cancer cells by decreasing phospho-cofilin (Ser3) and phospho-LIMK1 (Thr508) without changing the total expression of cofilin and LIMK1 . In addition, alkaloid 7 showed acaricidal and aphicidal effects on Tetranychus cinnabarinus and Aphis citricola , respectively, and antifungal activity against Botryosphaeria dothidea and Fusarium oxysporum …”
Section: Bioactivity Of Quinolizidine Alkaloids: An Overviewmentioning
confidence: 97%
See 4 more Smart Citations
“…Alkaloid 2 significantly inhibited migration and invasion of human gastric cancer cells by decreasing phospho-cofilin (Ser3) and phospho-LIMK1 (Thr508) without changing the total expression of cofilin and LIMK1 . In addition, alkaloid 7 showed acaricidal and aphicidal effects on Tetranychus cinnabarinus and Aphis citricola , respectively, and antifungal activity against Botryosphaeria dothidea and Fusarium oxysporum …”
Section: Bioactivity Of Quinolizidine Alkaloids: An Overviewmentioning
confidence: 97%
“…216 In addition, alkaloid 7 showed acaricidal and aphicidal effects on Tetranychus cinnabarinus and Aphis citricola, 217 respectively, and antifungal activity against Botryosphaeria dothidea 218 and Fusarium oxysporum. 219 It has been reported that the consumption of seeds from Lupinus plants containing alkaloid 62 has led to intoxication events in humans due to the acute anticholinergic toxicity of some lupanine-type QAs. The most common symptoms are blurred vision, dry mouth, easy flushing, and confusion.…”
Section: Quinolizidine Alkaloidsmentioning
confidence: 99%
See 3 more Smart Citations